(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Recently, a drug delivery system with controlled and targeted drug release at the tumor sites emerged as an attractive option for improving anticancer therapeutics. Advanced nanotherapeutics must not be limited to nanoscale, but should find their way to target the solid tumor via direct or indirect way. Pegylation on the surface of liposome helps to become liposome as long-circulating and indirect or passive targeting to tumors. The purpose of this study is to develop and optimize the critical process parameters, which play an important role in the quality pegylated liposome. The design of experiment (DoE) was used to study the impact of critical process variables like hydration temperature, extrusion process temperature, ethanol concentration, drug loading temperature, and drug loading time. Pegylated liposome was prepared using the ethanol injection method. Size reduction was achieved using the extrusion method. Drug encapsulation was achieved by a remote loading method using an ammonium phosphate gradient. A fractional factorial design was chosen for the optimization of process variables. Hydration temperature and extrusion process temperature directly impact on the degradation of lipids used in liposome formation. Higher temperature increases the lipid degradation during the process. The concentration of ethanol during the size reduction process inversely affects the particle size of the liposome. Higher the ethanol content lowers the particle size achieved. The temperature during drug loading process directly affects the degradation of the drug while inversely affect the encapsulation property. Stability study indicates that optimized formulation using DoE approach remains stable. The present research confirms the feasibility of developing and optimizing sterically stabilized liposome using DoE approach.